Analysis study of Methampyrone in jamu pegal linu circulating in Semarang City using Fourier Transform Infrared (FTIR) Spectrophotometry and UV-Vis Spectrophotometry - Ameliyana; Endah Widhihastuti (Journal of Science and Technology Research for Pharmacy, 2024)
Traditional medicine (jamu) has been widely known as an alternative medicine because its side effects are mild, easy to obtain, and cheaper than synthetic medicines. One of the herbal medicines used as a pain reliever in Indonesia is called Jamu Pegal linu. Analgesic drugs are often added illegally to herbal remedies to treat aches and pains. Methampyrone is an example of a medicinal chemical that can most likely be added to jamu pegal linu. The National Food and Drug Administration reported the discovery of contamination in the form of medicinal chemicals. The distribution of herbal medicines containing medicinal chemicals that are dangerous to the public is prohibited based on Minister of Health Regulation no. 007 of 2012. This study aims to determine the content and levels of the medicinal chemical methampyrone in jamu pegal linu in Semarang City. In this study, jamu pegal linu sold in Semarang City will be analyzed for the medicinal chemical content of methampyrone. This research is an experimental study to qualitatively and quantitatively analyze the medicinal chemicals of the drug methampyrone in jamu pegal linu. The qualitative analysis method uses FTIR to identify functional groups. The quantitative analysis method uses UV-Vis Spectrophotometry which has been validated to determine the levels of methampyrone contained in jamu pegal linu. The results of qualitative analysis tests using FTIR show that methampyrone contains functional groups such as C=O (amide), C=C (aromatic), C-H, O=S=O,  C-O, S=O, and C-H out-of-plane. The readings from the fifth samples (A, B, N, I, and L) were positive for methampyrone due to the presence of these functional groups, which are characteristic of methampyrone. Validation of the analytical method using UV-Vis Spectrophotometry demonstrates its suitability for quantifying methampyrone levels in jamu pegal linu. The method validation parameters include a correlation coefficient (R2) of 0.9997; limit of detection (LOD) of 0.275966 mg/L; limit of quantification (LOQ) of 0.9198867 mg/L; precision expressed as % RSD of 0.1444%; and accuracy indicated by %recovery of 82,7544%; 84,005%; and 85,721%. The results from the validated analysis method reveal the presence of methampyrone in jamu pegal linu across the five samples (A, B, N, I, and L), with concentrations in each sample measured at 3,594 ± 0,002%; 1,507 ± 0,003%; 1,386 ± 0,003%; 2,900 ± 0,003%; and 31,870 ± 0,028%.